IMPLEMENTASI PNPM MANDIRI PEDESAAN PADA PROGRAM SIMPAN PINJAM KHUSUS BAGI PEREMPUAN DI DESA PERANGAT SELATAN KECAMATAN MARANGKAYU - Rahmawati; Adam Idris; Farhanuddin Jamanie (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
The government launched a National Program for Empowering Rural Independent Communities (PNPM-PM in Indonesia) to increase the effectiveness of poverty reduction. One of them is thorugh a special savings and loan program for women. This research is a qualitative descriptive study. South Perangat Village, Marangkayu District, Kutai ertanegara Regency is the chosen research location. The research focus is determined based on the Presidential Regulation of the Republic of Indonesia Number 15 of 2010 concerning the Acceleration of Poverty Reduction. The results of the study indicate that the implementation of PNPM-MP in the Special Savings and Loan Program for Women has not run optimally. This is due to the lack of awareness of the borrowers of funds to develop the business they have put forward in the proposal, even though the loan funds have been obtained. The research findings show that every month there are still arrears in loan payment to the Activity Management Unit team. The obstacle in implementing the program is that there is no evaluation by the Activity Management Unit team of this program.